SISTEM KEKERABATAN MATRILINEAL DALAM MITOS “MALIN KUNDANG” - Fitriana, Yulita (Universitas Lancang Kuning, 2018)
This study aims to know the problem solving of economy, socio-culture, and religion in respect to matrilineal concept of Minangkabau society. The problems raised in this study are about the problem of economy, socio-culture, and religion related to matrilineal concept. The result of study proves that the “surface structure” that belongs to this story contained “deep structure” that reflects the cultural identity of the matrilineal society of Minangkabau. This study uses a qualitative approach. Data obtained through library research with the presentation of descriptive data analysis. After investigation, It can be concluded that the matrilineal kinship system in Minangkabau society affects the way the society in addressing the problems that arise, as seen in the myth of “Malin Kundang”. The myth illustrates matters as follows. 1. The economic issues that arise is solved by wandering famous tradition in Minang community. 2. After marriage, a man will stay in the family of woman (matrilocal). If the opposite happens, it becomes a disgrace to the family. 3. Punishment of Malin Kun-dang figures closely associated with the position of Minangkabau women who are considered high in society, in the tradition and values of Islam exposed by Minangkabau community.